Pestivirus Infections in Semi-Domesticated Eurasian Tundra Reindeer (Rangifer tarandus tarandus): A Retrospective Cross-Sectional Serological Study in Finnmark County, Norway. - Neves, Carlos Gonzalo das; Johansson Wensman, Jonas; Nymo, Ingebjørg Helena; Skjerve, Eystein; Alenius, Stefan; Tryland, Morten (Viruses, 2019)
Members of the Pestivirus genus (family Flaviviridae ) cause severe and economically important diseases in livestock. Serological studies have revealed the presence of pestiviruses in different cervid species, including wild and semi-domesticated Eurasian tundra reindeer. In this retrospective study, serum samples collected between 2006 and 2008 from 3339 semi-domesticated Eurasian reindeer from Finnmark County, Norway, were tested for anti-pestivirus antibodies using an enzyme linked immunosorbent assay (ELISA) and a subset of these by virus neutralization test (VNT). A seroprevalence of 12.5% was found, varying from 0% to 45% among different herding districts, and 20% in western Finnmark, as compared to 1.7% in eastern Finnmark. Seroprevalence increased with age. Pestivirus-specific RNA was not detected in any of the 225 serum samples tested by real-time RT-PCR. Based on VNT results, using a panel of one bovine viral diarrhea virus (BVDV) strain and two border disease virus (BDV) strains, the virus is most likely a reindeer-specific pestivirus closely related to BDV. A characterization of the causative virus and its pathogenic impact on reindeer populations, as well as its potential to infect other domestic and wild ruminants, should be further investigated